2017
DOI: 10.1089/cbr.2017.2268
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-497-5p Suppresses Tumor Cell Growth of Osteosarcoma by Targeting ADP Ribosylation Factor-Like Protein 2

Abstract: Taken together, our findings revealed miR-497-5p may be a tumor suppressor in OS and serve as a promising therapeutic target for OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…Previous studies have shown that miR‐497‐5p is of great interest in cancer therapies due to its association with various types of cancer (Chai et al, ; Chen et al, ; Sun et al, ). Here, we found that low miR‐497‐5p expression in HCC tissues was significantly correlated with poor prognosis of patients; thus, we focused on the roles and corresponding mechanisms of miR‐497‐5p in the progression of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that miR‐497‐5p is of great interest in cancer therapies due to its association with various types of cancer (Chai et al, ; Chen et al, ; Sun et al, ). Here, we found that low miR‐497‐5p expression in HCC tissues was significantly correlated with poor prognosis of patients; thus, we focused on the roles and corresponding mechanisms of miR‐497‐5p in the progression of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study provides a novel solution to break the physiological and cellular barriers to deliver microRNAs [32]. Previous study show that miR-497-5p was significantly down-regulated in osteosarcoma and it suppresses tumour growth by targeting ADP ribosylation factor-like protein 2 [33]. Similarly, miR-497-5p was significantly down-regulated in glioma tissues and it targets SOX9 to inhibit proliferation, migration and invasion [34].…”
Section: Discussionmentioning
confidence: 99%
“…miR-5590-3p suppresses the gastric tumorigenesis by negatively regulating DDX5/AKT/m-TOR pathway [5]. Recently, some studies have shown that miR-497-5p functions as a tumor suppressive miRNA in various cancers, including melanoma [6], osteosarcoma [7] and angiosarcoma [8]. The hTERT, ADP ribosylation factor-like protein 2 and KCa3.1 are potential target of miR-497-5p in these cancers.…”
Section: Introductionmentioning
confidence: 99%